2021
DOI: 10.1002/ps.6640
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of nucleopolyhedrovirus with polydopamine to improve its properties

Abstract: BACKGROUND: Baculoviruses have been developed as promising biopesticides to control pests due to their high host specificity and virulence, and nontoxicity to humans and nontarget animals. However, their sensitivity to ultraviolet (UV) radiation and instability in the natural environment are major constraints to its large-scale application. In this study, polydopaminenucleopolyhedrovirus microcapsules were established to improve the instability of baculoviruses in sunlight. RESULTS:The optimal conditions for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The spore viability and mortality toward Ephestia kuehniella larvae were 68% and 85%, respectively, whereas the spore viability and larval mortality of the free spore formulation were 40% and 50%, respectively. Previous research has shown that the insecticidal activity against Spodoptera exigua larvae of nonmicroencapsulated baculovirus was reduced by 27.27% under UV treatment, whereas that of the microencapsulated baculovirus was only reduced by 8.89% ( 34 ). In conclusion, microencapsulation of biological control products results in significantly improved stability and viability of conidia even under UV irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…The spore viability and mortality toward Ephestia kuehniella larvae were 68% and 85%, respectively, whereas the spore viability and larval mortality of the free spore formulation were 40% and 50%, respectively. Previous research has shown that the insecticidal activity against Spodoptera exigua larvae of nonmicroencapsulated baculovirus was reduced by 27.27% under UV treatment, whereas that of the microencapsulated baculovirus was only reduced by 8.89% ( 34 ). In conclusion, microencapsulation of biological control products results in significantly improved stability and viability of conidia even under UV irradiation.…”
Section: Discussionmentioning
confidence: 99%